Iron chelation: an adjuvant therapy to target metabolism, growth and survival of murine PTEN-deficient T lymphoma and human T lymphoblastic leukemia/lymphoma. Issue 6 (3rd June 2017) - Benadiba, Joy; Rosilio, Celia; Nebout, Marielle; Heimeroth, Vera; Neffati, Zouhour; Popa, Alexandra; Mary, Didier; Griessinger, Emmanuel; Imbert, Véronique; Sirvent, Nicolas; Peyron, Jean-François
Abstract: Iron is an essential nutrient, acting as a catalyst for metabolic reactions that are fundamental to cell survival and proliferation. Iron complexed to transferrin is delivered to the metabolism after endocytosis via the CD71 surface receptor. We found that transformed cells from a murine PTEN-deficient T-cell lymphoma model and from T-cell acute lymphoblastic leukemia/lymphoma (T-ALL/T-LL) cell lines overexpress CD71. As a consequence, the cells developed an addiction toward iron whose chelation by deferoxamine (DFO) dramatically affected their survival to induce apoptosis. Interestingly, DFO displayed synergistic activity with three ALL-specific drugs: dexamethasone, doxorubicin, and L-asparaginase. DFO appeared to act through a reactive oxygen species-dependent DNA damage response and potentiated the action of an inhibitor of the PARP pathway of DNA repair. Our results demonstrate that targeting iron metabolism could be an interesting adjuvant therapy for acute lymphoblastic leukemia.